2012
DOI: 10.1091/mbc.e12-06-0424
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokine secretion is suppressed by TMEM16A or CFTR channel activity in human cystic fibrosis bronchial epithelia

Abstract: Functional expression of either CFTR or the calcium-activated chloride channel TMEM16A attenuates expression and secretion of the proinflammatory cytokines IL-6, IL-8, and CXCL1/2 in respiratory epithelia. Thus augmented proinflammatory cytokine secretion caused by defective anion transport may contribute to lung inflammation in cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 84 publications
6
126
0
Order By: Relevance
“…That CFTR is a negative regulator of NF-kB with inherent antiinflammatory properties is an emerging concept (8,(63)(64)(65), although it is still controversial (66). Our secretome data support the concept of increased endogenous NF-kB hyper-activity in CF HBE cells at ALI: as many of the 20 most highly differentially abundant secreted proteins are up-regulated by NF-kB.…”
Section: Concluding Commentssupporting
confidence: 63%
“…That CFTR is a negative regulator of NF-kB with inherent antiinflammatory properties is an emerging concept (8,(63)(64)(65), although it is still controversial (66). Our secretome data support the concept of increased endogenous NF-kB hyper-activity in CF HBE cells at ALI: as many of the 20 most highly differentially abundant secreted proteins are up-regulated by NF-kB.…”
Section: Concluding Commentssupporting
confidence: 63%
“…Nonetheless, we note that ANO1 (TMEM16A) overexpression has been shown to suppress proinflammatory cytokine expression in human cystic fibrosis bronchial epithelia (44). Another study identified an activated immune response specific to the pancreas in newborn pigs with cystic fibrosis (45).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, novel corrector molecules targeting either the NBD1 and/or its interface defects should be preferentially identified by screening in the background of VX-809 or the interface-stabilizing mutation R1070W. To this end, we established a novel biochemical screening procedure using human lung epithelium-derived cell lines (CFBE41o 2 ; Ehrhardt et al, 2006;Veit et al, 2012). Compounds were identified that increased correction efficacy when combined with VX-809 beyond that of maximal VX-809 alone, supporting the idea of synergy screening and corrector combination therapy for CF caused by the ΔF508 mutation.…”
Section: Introductionmentioning
confidence: 99%